2015
DOI: 10.1016/j.jpainsymman.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Capture, Transfer, and Feedback of Patient-Centered Outcomes Data in Palliative Care Populations: Does It Make a Difference? A Systematic Review

Abstract: In palliative care populations, PCOMs feedback improves awareness of unmet need and allows professionals to act to address patients' needs. It consequently benefits patients' emotional and psychological quality of life. However, more high-quality evidence is needed in noncancer populations and across a wider range of settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
228
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(235 citation statements)
references
References 48 publications
5
228
0
2
Order By: Relevance
“…57 There is also one review of qualitative studies 58 and four mixed-method reviews. [59][60][61][62] Thus, there are a total of 21 existing reviews examining the feedback of individual PROMs data in patient care. Of these reviews, one focused on screening for mental health problems 51 in primary and secondary care, and four others focused on the use of PROMs feedback in specialist mental health settings.…”
Section: Existing Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…57 There is also one review of qualitative studies 58 and four mixed-method reviews. [59][60][61][62] Thus, there are a total of 21 existing reviews examining the feedback of individual PROMs data in patient care. Of these reviews, one focused on screening for mental health problems 51 in primary and secondary care, and four others focused on the use of PROMs feedback in specialist mental health settings.…”
Section: Existing Evidencementioning
confidence: 99%
“…A number of reviews had already focused on the practical or logistical aspects of PROMs implementation. 59,60 Furthermore, a review has recently been published exploring electronic patient-reported outcomes (ePROs). We decided to focus our review on exploring system strains 1 (individualised vs.…”
Section: How Clinicians Might Use Patient-reported Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have described their ideas and approaches for, experience and outcomes with, and barriers to developing successful programs that integrate palliative care into routine oncologic care. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] A recent systematic review found evidence that capture and feedback of patient centred outome measures improves symptom recognition and favourably impacts on care processes. [15] To date there are no published articles on the routine use of PROMS in the SPDC setting. In this article we describe our experience using a combination of both patient and carer rated tools to monitor patient outcomes in our SPDC unit which operates an enhanced therapeutic model.…”
Section: Introductionmentioning
confidence: 99%